2020
DOI: 10.1007/s12975-020-00877-y
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Recanalization—How Late Is Not Too Late?

Abstract: Stroke has become the second most prevalent cause of mortality in the world. Currently, the treatment of ischemic stroke is based on thrombolytic and thrombectomy therapy shortly after the ischemic event (≤ 4.5 h for thrombolytic strategies; ≤ 6 h for thrombectomy strategies). However, the majority of patients are unable to receive prompt treatment, particularly in undeveloped countries. Alternative solutions are lacking for those patients that miss the optimal window of opportunity for treatment. Recently, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…In support of this hypothesis, one study recently reanalyzed the data from the DEFUSE 3 study and suggested that about 20% of ischemic stroke patients with LVO who are not treated with thrombectomy had a persistent mismatch of up to 48 hours [ 20 ]. Subsequently, numerous case reports suggest a functional association between delayed blood flow restoration and neurological outcome conditional to imaging mismatch beyond 3 days from symptom onset [ 46 , 47 ]. In this study, using ischemia durations of 3 days, we validated the effect of delayed recanalization on neurological deficits and the underlying mechanisms driving these effects in a rat MCAO model.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, one study recently reanalyzed the data from the DEFUSE 3 study and suggested that about 20% of ischemic stroke patients with LVO who are not treated with thrombectomy had a persistent mismatch of up to 48 hours [ 20 ]. Subsequently, numerous case reports suggest a functional association between delayed blood flow restoration and neurological outcome conditional to imaging mismatch beyond 3 days from symptom onset [ 46 , 47 ]. In this study, using ischemia durations of 3 days, we validated the effect of delayed recanalization on neurological deficits and the underlying mechanisms driving these effects in a rat MCAO model.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, for many years, most AIS patients were prevented from receiving effective recanalization therapy because of a narrow therapeutic window. In recent years, a series of clinical trials have indicated that delayed recanalization may still have benefits in ischemic brains during an expanded therapeutic window, up to more than 24 h, several days, and even more than 1 month after symptom onset [Reviewed by Kang et al (2020) ].…”
Section: Pathophysiology Of Ischemic-reperfusion Injury ( Figure 2 )mentioning
confidence: 99%
“…The incidence of ischemic stroke, which is the second cause of mortality and dementia in older individuals, is increasing annually worldwide [ 1 , 2 ]. More than 50% of stroke patients will have cognitive impairment in clinic, and about 10% of them will have dementia, which seriously affects their prognosis and quality of life [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%